Carrots over Sticks? Mothers' Pensions and Child Labor in the Early 20th Century U.S. Issue 2 (23rd March 2023) - Anderson, Elisabeth; Kornrich, Sabino; Abdelhadi, Eman
Abstract: While existing research suggests that nineteenth-century child labor laws largely failed to significantly reduce children's workforce participation, we examine whether policies that tackled the problem by providing aid – rather than by penalizing work – were more effective. Between 1910 and 1920, forty U.S. states enacted mothers' pension programs, giving needy "deserving" mothers, typically widows, cash aid to support their dependent children. One purpose of the programs was to reduce child labor. However, we find no negative relationship between child labor and the generosity of states' mothers' pension laws. Furthermore, we find no negative relationship between child labor and county-level mothers' pension generosity, in terms of expenditures, in the seven states for which we have data. We attribute this to the small size of the pensions as well as the programs' limited coverage and general lack of conditionality on children's behaviors, such as attending school or not engaging in paid work. We also note states' and counties' limited administrative capacity to enforce eligibility requirements, such as school attendance, where these existed.